Biogenic Iron Preserves Structures during Fossilization: A Hypothesis: Iron from Decaying Tissues May Stabilize Their Morphology in the Fossil Record. (27th April 2020) - Saleh, Farid; Daley, Allison C.; Lefebvre, Bertrand; Pittet, Bernard; Perrillat, Jean Philippe
Abstract: It is hypothesized that iron from biological tissues, liberated during decay, may have played a role in inhibiting loss of anatomical information during fossilization of extinct organisms. Most tissues in the animal kingdom contain iron in different forms. A widely distributed iron‐bearing molecule is ferritin, a globular protein that contains iron crystallites in the form of ferrihydrite minerals. Iron concentrations in ferritin are high and ferrihydrites are extremely reactive. When ancient animals are decaying on the sea floor under anoxic environmental conditions, ferrihydrites may initialize the selective replication of some tissues in pyrite FeS2 . This model explains why some labile tissues are preserved, while other more resistant structures decay and are absent in many fossils. A major implication of this hypothesis is that structures described as brains in Cambrian arthropods are not fossilization artifacts, but are instead a source of information on anatomical evolution at the dawn of complex animal life. Abstract : Nervous systems are preserved in numerous fossils in the absence of more resistant tissues, despite the fast degradation of nervous tissues in laboratory conditions. It is hypothesized that a biogenic source of iron initiated the preservation of these labile structures in pyrite (FeS2 ). This hypothesis suggests that preserved patterns in fossils are not artifacts but rather a source for evolutionary information.